Characteristics of blood lipid and metabolic indicators in subclinical hypothyroidism patients: a retrospective study - Zhu, Lili; Jiang, Xiaohong (Frontiers in Medicine, 2024)
Background: The characteristics of blood lipid and metabolic indicators were characterized in patients with subclinical hypothyroidism (SCH) and the effect of type 2 diabetes mellitus (T2DM) on SCH patients was determined. Methods: The physical examination data of 2119 residents in a university community were retrospectively divided into 2 groups (SCH and non-SCH groups). Furthermore, the SCH group was divided into SCH-T2DM and SCH-non-T2DM subgroups and the data between the groups were analyzed. Results: The SCH group had significantly higher levels of triglycerides (P=0.044), total cholesterol (P=0.001), low-density lipoprotein-cholesterol (P=0.019), very low-density lipoprotein-cholesterol (P=0.044), 2-h plasma glucose (P=0.023), and globulin (P=0.000) compared to the non-SCH group. The SCH-T2DM group was older (P<0.001), had a greater BMI (P=0.028), a more rapid heart rate (P=0.025), and a greater waist circumference (P<0.001) than the SCH-non-T2DM group based on the subgroup analysis. The SCH-T2DM group had a significantly higher dyslipidemia and dysglycemia levels than the SCH-non-T2DM group. Conclusion: Patients with SCH with or without T2DM may have dyslipidemia and dysglycemia and should be evaluated accordingly.